THEORETICAL FOUNDATIONS OF RESEARCH ON MARITAL RELATIONSHIPS AND VALUES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the theoretical foundations of research on marital relationships and values. It examines key psychological theories and conceptual frameworks that help understand the dynamics of marital interaction, emotional connection, and value alignment between partners. The study highlights the importance of mutual respect, communication, and shared beliefs in maintaining a healthy marital relationship. Additionally, the article reviews contemporary research findings, discusses cultural influences on marital values, and emphasizes the role of psychological support in enhancing marital satisfaction and stability.